The California Tobacco Control Program's effect on adult smokers: (1) Smoking cessation. Issue 2 (30th March 2007) - Messer, Karen; Pierce, John P; Zhu, Shu-Hong; Hartman, Anne M; Al-Delaimy, Wael K; Trinidad, Dennis R; Gilpin, Elizabeth A
Abstract : Objectives: To estimate national population trends in long-term smoking cessation by age group and to compare cessation rates in California (CA) with those of two comparison groups of states. Setting: Retrospective smoking history of a population sample from the US: from CA, with a comprehensive tobacco-control programme since 1989 with the goal of denormalising tobacco use; from New York and New Jersey (NY & NJ), with similar high cigarette prices but no comprehensive programme; and from the tobacco-growing states (TGS), with low cigarette prices, no tobacco-control programme and social norms relatively supportive of tobacco use. Participants: Respondents to the Current Population Survey–Tobacco Use Supplements (1992–2002; n = 57 918 non-Hispanic white ever-smokers). Main outcome measures: The proportion of recent ever-smokers attaining long-term abstinence (quit ⩾1 year) and the successful-quit ratio (the proportion of all ever-smokers abstinent ⩾1 year). Results: Nationally, long-term cessation rates increased by 25% from the 1980s to the 1990s, averaging 3.4% per year in the 1990s. Cessation increased for all age groups, and by >40% (p<0.001) among smokers aged 20–34 years. For smokers aged <50 years, higher cigarette prices were associated with higher quitting rates. For smokers aged <35 years, quitting rates in CA were higher than in either comparison group (p<0.05). Half of the ever-smokers had quit smoking by age 44 years in CA, 47 years in NY & NJ, and by age 54 years in TGS. Conclusion: Successful smoking cessation increased by 25% during the1990s in the US. Comprehensive tobacco-control programmes were associated with greater cessation success than were with high cigarette prices alone, although both effects were limited to younger adults.